2008
DOI: 10.1155/2008/474618
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics Determine Health-Related Quality of Life as an Outcome Indicator of Geriatric Inpatient Rehabilitation

Abstract: Background. The aim of the present study was to investigate the relationships between personality and quality of life during the course of geriatric rehabilitation, against the background of Cloninger's biosocial theory of personality. Methods. All consecutive patients of a geriatric rehabilitation clinic during one year were evaluated at admission and discharge (N = 687) by means of the ‘‘Vienna List’’ (a newly developed questionnaire for the assessment of quality of life in patients with severe dementia), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This is consistent with a previous study of our group, indicating higher levels of HA in BPD patients, whereas values for NS were not elevated (Barnow et al, 2005; Barnow et al, 2007). Furthermore, these findings are in line with the assumption of several authors, emphasizing that affective instability/negative affectivity, constructs which have been shown to be related to HA (Livesley, Jang, & Vernon, 1998; Richter, Schwarz, & Bauer, 2008), are the primary core underlying features of BPD that drives other symptoms of BPD, such as impulsivity, which is a component of NS (Linehan 1993; Brown, Comtois, & Linehan, 2002; Tragesser, Solhan, Schwartz‐Mette, & Trull, 2007). Recent empirical evidence supports this conceptualization.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a previous study of our group, indicating higher levels of HA in BPD patients, whereas values for NS were not elevated (Barnow et al, 2005; Barnow et al, 2007). Furthermore, these findings are in line with the assumption of several authors, emphasizing that affective instability/negative affectivity, constructs which have been shown to be related to HA (Livesley, Jang, & Vernon, 1998; Richter, Schwarz, & Bauer, 2008), are the primary core underlying features of BPD that drives other symptoms of BPD, such as impulsivity, which is a component of NS (Linehan 1993; Brown, Comtois, & Linehan, 2002; Tragesser, Solhan, Schwartz‐Mette, & Trull, 2007). Recent empirical evidence supports this conceptualization.…”
Section: Discussionsupporting
confidence: 90%
“…Self-directedness has been considered as the most important character trait attributed to well-being, life satisfaction, and QoL [5153]. Studies have found a positive correlation with QoL in clinical patients with schizophrenia and schizoaffective disorder [54], attention deficit and hyperactivity disorder [55], and in samples of psychiatric outpatients [53] and geriatric inpatients [56]. In our study, it was specifically a predictor of psychological QoL, described as emotional and mental wellness, and environmental QoL, described as external resources and opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…sense of coherence, mastery, self-efficacy) 9,10 . Some research instead included scales for the assessment of personality based on specific theories, the most commonly used among which are the Eysenck Personality Questionnaire (EPQ) 8,9 , the NEO Five-Factor Inventory 5,10 , and the Temperament Character Inventory [11][12][13] . These studies highlighted the complex and heterogeneous nature of the relationship between personality and QoL.…”
Section: Introductionmentioning
confidence: 99%